Parent and household influences on calcium intake among early adolescents - Jinan Banna; Jessica O'Driscoll; Carol J. Boushey; Garry Auld; Beth Olson; Mary Cluskey; Miriam Edlefsen Ballejos; Christine Bruhn; Scottie Misner; Marla Reicks; Siew Sun Wong; Sahar Zaghloul (BMC, 2018)
Abstract Background Calcium intake during early adolescence falls short of requirements for maximum bone accretion. Parents and the home food environment potentially influence children's calcium intakes. This study aimed to quantify parental psychosocial factors (PSF) predicting calcium intakes of Asian, Hispanic, and non-Hispanic white (NHW) early adolescent children from a parental perspective. Methods This was a cross-sectional study involving the administration of a validated calcium-specific food frequency questionnaire to a convenience sample of children aged 10-13 years and the primary individual responsible for food acquisition in the child's household. Based on Social Cognitive Theory, parental factors potentially associated with children's calcium intake were also assessed via parent questionnaires. The total study sample consisted of 633 parent-child pairs (Asian = 110, Hispanic = 239, NHW = 284). Questionnaires were completed at community-based centers/sites. Outcome measures were the association between parent-child calcium (mg), milk (cups/day), and soda (cans/day) intakes and the predictive value of significant parental PSF towards calcium intakes of their children. Sex-adjusted linear regression and multivariate analyses were performed. Results Calcium intakes of parent-child pairs were positively associated among all ethnic groups (r = 0.296; P < 0.001). Soda intakes were positively associated among Hispanic parent-child pairs only (r = 0.343; P < 0.001). Home availability of calcium-rich foods (CRF), parental rules and expectations for their child's intake of beverages, and parents' calcium intake/role modeling were positively associated with children's calcium intake and overwhelmed all other PSF in multivariate analyses. Significant cultural differences were observed. Parental role modeling was a significant factor among Hispanic dyads only. Multivariate models explained 19-21% of the variance in children's calcium intakes. Conclusions Nutrition interventions to improve children's calcium intakes should focus on parents and provide guidance on improving home availability of CRF and increasing rules and expectations for the consumption of CRF. Among Hispanic families, interventions promoting parental modeling of desired dietary behaviors may be most successful.